Zimbabwe Economic Policy Dialogue : Policy Notes for the New Government - 2013 - World Bank (Washington, DC, 2015)
In past four years, the World Bank, in close cooperation with the Government of Zimbabwe, and the support of international partners - has carried out a number of studies and technical assistance activities in key areas of the socio-economic recovery. In line with Bank’s Africa strategy of fostering Africa’s economic transformation and poverty reduction, the overall goal of these studies has been to support broad-based development of Zimbabwe by facilitating evidence-based debate and policy-making. As a new government for 2013-2018 is about to take function, sectoral teams at the World Bank have distilled key analysis from those studies, and prepared the short policy notes. The policy notes attempt to summarize the main findings, challenges, constraints, and lay out policy options. While the past decade of hyperinflation and weak economic management has undoubtedly eroded a significant share of Zimbabwes physical and human capital, these can be rebuilt with the combination of sound economic policy and proper incentives to private sector investors, both domestic and foreign. It is therefore imperative that, however policymakers choose to proceed with regard to the future direction of the economy, they deliver well-articulated, credible, and stable economic policies. Such policies will enable and unleash the creative energies and entrepreneurial spirit of the private sector, the one that has delivered so often in the past. The policy note highlights the breadth and complexity of challenges in fostering long-term development. Addressing these challenges is a long haul task that will require a good sense of overarching priorities, as well as strong commitment to long-term objectives and policy consistency.